Congenital adrenal hyperplasia: an update in children - Trapp, Christine M. (2011)
PURPOSE OF REVIEW: Congenital adrenal hyperplasia (CAH) in children, the majority of which is due to 21-hydroxylase deficiency, represents a group of disorders in which there is impaired cortisol synthesis and abnormalities in adrenal hormonal profiles. There continues to be debate regarding the optimal management of and treatment for these children. This review will highlight the most recent advances in neonatal screening for CAH, as well as the timeliest recommendations for the treatment and management of 21-hydroxylase deficiency, both the classic and non-classic forms of the disorder. RECENT FINDINGS: Substantive advancements have been made with regards to neonatal screening for CAH, allowing for earlier diagnosis while minimizing the morbidity and mortality associated with delayed detection. While the achievement of normal growth and development remains the ultimate goal of treatment, recent studies have provided further insight into the management and refinement of therapy in these children. SUMMARY: The optimal management and treatment for children with CAH is still unclear. While there have been recent advances in the diagnosis and treatment of this group of disorders, there is still much to learn in order to optimize therapy for these individuals.